Implementasi Kebijakan Zonasi dan Kurikulum Merdeka serta Implikasinya terhadap Numerasi Siswa - Ulfa Aldayanti; Bambang Sri Anggoro; Rosida Rakhmawati (AB-JME: Al-Bahjah Journal of Mathematics Education, 2026)
This study aims to analyze the implementation of the zoning policy and the Independent Curriculum and their implications for junior high school students' numeracy skills. The background of this study is based on the gap between the quantitative increase in numeracy achievement and the still suboptimal quality of learning. This study used a qualitative approach with a case study design conducted from January–March 2026 at a public junior high school in Bandar Lampung City. Research informants consisted of the principal, vice principal for curriculum, mathematics teachers, and other subject teachers involved in the implementation of the Independent Curriculum. Data were collected through in-depth interviews, learning observations, and documentation in the form of Education Report Cards, National Assessment results, teaching modules, and school policy documents. Data were analyzed using the General Inductive Analysis (GIA) approach. The results of the study indicate that the zoning policy has implications for the heterogeneity of students' academic abilities and learning motivation, while the Independent Curriculum provides space for more flexible, contextual, and differentiated learning. However, its implementation still faces obstacles such as limited learning time, teacher pedagogical readiness, limited facilities, and variations in student abilities. The findings also indicate a gap between the increase in numeracy scores from 66.67 in 2023 to 95.56 in 2024 and the quality of learning, which remains in the moderate category. This study concludes that strengthening numeracy requires synergy between policies, teacher preparedness, adaptive learning strategies, facility support, and a conducive learning environment.